The Clarion of Syria A Patriot's Call against the Civil War of 1860 - Al-Bustani, Butrus (University of California Press, 2019)
When "The Clarion of Syria" was penned, between September 1860 and April 1861, its anonymous author-identified only as "a patriot"-had just witnessed his homeland undergo unprecedented violence in what many today consider Lebanon's first civil war. Butrus al-Bustani, the author, wrote a series of pamphlets to his fellow Syrians that became a key text of the nineteenth-century literary revival movement known as the Nahda. They addressed an array of universally resonant and locally relevant themes that render the pamphlets pertinent beyond their immediate context. With a style oscillating between Paulinian sermon and Socratic dialogue, the author ponders the meaning of civil war in relation to religion, politics, morality, society, and civilization. Above all, the text was an anti-sectarian clarion call to build a cohesive and "civilized" Syrian society in place of what the author considered a community gripped by the most pernicious of conflicts, violent fanaticism and factionalism. Rereading the pamphlets in the context of today's political violence in war-torn Syria and elsewhere in the Arab world helps us gain a critical and historical perspective on (anti-)sectarianism, conflict resolution, Western interventionism, and national reconciliation. This translation thereby makes an important historical document accessible for the first time to an English audience.